As convenções processuais e o papel do magistrado em um modelo cooperativo de processo - Saraiva, Diogo de Oliveira (2022)
The present work aims at the study of procedural conventions and their applicability through the collaborative process. Law 13.105/2015 (Code of Civil Procedure) innoted by conferring the possibility of atypical procedural conventions, through an open clause positive in article 190, allowing the parties greater autonomy in the procedure to adapt it to the specificities of the cause. This way, the present work deals with the specific theme of procedural conventions through a historical evolution of civil procedural law, beginning in the Roman litiscontestatio, from which a subjective parallel of similarity is drawn in the theme under focus, considering that means of conflict resolution the parties had great interference in their criation. It details the evolution of the theme from the emergence of the civil process as a matter dissociated from subjective law, with an initial focus on Bülow's ideas, going through the construction (and denial) of doctrine in countries such as Germany, Italy, France and, mainly, the development of the subject in Brazil. After establishing the evolutionary bases, we seek to deal with procedural conventions in their contours, their distinction from the legal business of material law to the limits imposed by the system. It analyzes the figure of the magistrate, his powers and the form of which he relates to procedural conventions, aiming at his intervention as a promoter. Combining the procedural conventions with the managerial power of the magistrate, it enables the study of its implementation through the cooperative process, described in Article 6 of the Code of Civil Procedure, deducing modern ways of conducting the course that allow greater effectiveness in the result